Konstruksi Pendidikan Karakter Kerja Keras(Analisis Isi pada Film "Jokowi" sebagai Media Pembelajaran Pendidikan Pancasila dan Kewarganegaraan) - Hidayat, Ali Nur (2016)
This study aimed to describe the character education construction hard work in the film "Jokowi". Background character education research that hard work can be obtained through media such as film, for example, because the films contain various moral message that can be taken the positive value and applied in real life. The hard work is needed by every individual to be able to achieve my goals and dreams. This research is a qualitative research. The method used is descriptive content analysis. Through words, scenes, and the messages conveyed in the film are the characters of hard work will be described using descriptive content analysis of the film "Jokowi". The result of this research is the construction of character education the hard work on the film "Jokowi" and content analysis. These results indicate that there are four indicators that show the character of hard work covers tend to maximize the potential of the completion of a task or job, emerged as a form of encouragement a strong motivation and the future orientation of the obvious, it is usually always think positive and not easily broken by obstacles that prevented, Indispensable amid increasingly dynamic world, competition, and competition is getting sharper.